A lithium-sodium dual-ion all-solid-state battery and a preparation method thereof

CN122992148APending Publication Date: 2026-10-27CHERY AUTOMOBILE CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611257229.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-18
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]本发明的目的在于提供一种锂钠双离子全固态电池及其制备方法,以解决现有技术中:锂钠双离子电池中单一电极材料无法同时适配锂、钠双离子差异化嵌脱行为导致双离子储荷位点不足、容量利用率低的问题;固态电解质配比固定不可调导致无法与电极活性组分精准匹配、锂离子电导率偏低、双离子传输失衡的问题;正极、电解质层、负极之间缺乏连续贯通的离子传输通道导致界面阻抗高、离子传输受阻的问题;以及传统液态电解液体系存在安全性差、低温工况性能严重衰减的问题

Benefits of technology

(1)本申请独创的钒基双材料复配正极、碳基双材料复配负极,可完美适配锂钠双离子差异化嵌脱行为,正极兼顾高电压与晶格稳定性,负极提供充足双离子储荷位点并抑制体积形变。相较于传统单一电极材料,本申请双离子有效利用率提升10%~18%,体积能量密度较纯钠基全固态电池提升15%以上,彻底解决传统双离子电池双离子不兼容、容量偏低的缺陷。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992148A_ABST
    Figure CN122992148A_ABST
Patent Text Reader

Abstract

The application discloses a lithium-sodium dual-ion all-solid-state battery, which is a layered all-solid-state stacking structure formed by sequentially adhering and pressing a positive electrode sheet, a lithium-sodium dual-ion mixed solid electrolyte film layer and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode main material and a first lithium-sodium dual-ion mixed solid electrolyte, the positive electrode main material is a vanadium-based polyanion sodium salt compounded with a vanadium-based polyanion lithium salt at a mass ratio of 1:1 to 1:5; and the negative electrode sheet comprises a negative electrode main material and a second lithium-sodium dual-ion mixed solid electrolyte, the negative electrode main material is a silicon-carbon material compounded with a soft carbon material at a mass ratio of 1:1 to 1:5. Through the special synergistic electrode system of the vanadium-based polyanion sodium salt compounded with the vanadium-based polyanion lithium salt for the positive electrode and the silicon-carbon compounded with the soft carbon for the negative electrode, the core problem that a traditional single electrode material cannot simultaneously adapt to the differential embedding and stripping behaviors of lithium and sodium dual ions is effectively solved, and the reversible storage utilization rate of the dual ions and the stability of the electrode structure are both significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium battery technology, and more specifically, to a lithium-sodium dual-ion all-solid-state battery and its preparation method. Background Technology

[0002] Lithium-ion batteries, with their high energy density, long cycle life, and excellent rate performance, have been widely used in new energy vehicles, large-scale energy storage, and portable electronic devices, becoming the most mature commercially available rechargeable battery system. However, lithium resources are limited in quantity and unevenly distributed in the Earth's crust. In recent years, the price of lithium raw materials has fluctuated dramatically, significantly increasing the production cost of lithium-ion batteries and hindering their large-scale adoption in cost-sensitive scenarios such as low-cost large-scale energy storage and low-speed transportation. To address this predicament, sodium-ion batteries have emerged. Leveraging the abundant and inexpensive nature of sodium resources, their good low-temperature performance, and outstanding fast-charging characteristics, they have become an important low-cost alternative to lithium batteries, and their industrialization process has accelerated significantly in recent years. However, sodium-ion batteries also have inherent limitations. Because the radius of sodium ions is significantly larger than that of lithium ions, the electrode insertion / extraction dynamics are relatively slow, resulting in weaker energy density, cycle stability, and high-voltage performance compared to traditional lithium-ion batteries. This makes it difficult to meet the requirements of high-end energy storage and power equipment for long-term operation and extended lifespan.

[0003] To balance cost and performance, the industry has begun exploring lithium-sodium dual-ion battery systems. These systems introduce lithium and sodium dual cations into the electrolyte to achieve synergistic charge storage, attempting to combine the high energy density of lithium batteries with the low cost of sodium batteries. Meanwhile, all-solid-state batteries, with their outstanding characteristics such as no liquid electrolyte, no leakage risk, non-flammability and non-explosion, strong high-voltage stability, and high upper energy density, fundamentally solve the safety hazards of traditional liquid batteries, including electrolyte evaporation, thermal runaway, and numerous interfacial side reactions. They are considered the core development direction for next-generation high-safety, high-energy-density batteries. Against this backdrop, lithium-sodium dual-ion all-solid-state batteries, which combine the lithium-sodium dual-ion system with an all-solid-state structure, have become a hot research topic in the industry.

[0004] In the prior art, patent CN111423647B discloses a method for preparing a lithium-sodium ion hybrid solid electrolyte and a solid hybrid battery. It uses a NASICON-structured ion exchange product as the hybrid solid electrolyte, with a single lithium iron phosphate cathode and metallic sodium anode. While achieving the basic configuration of an all-solid-state lithium-sodium hybrid battery, both the cathode and anode use a single active material. The fixed lattice structure of the lithium iron phosphate cathode cannot simultaneously meet the differentiated requirements of rapid small-radius lithium-ion insertion / extraction and stable large-radius sodium-ion storage, resulting in a significant mismatch in dual-ion insertion / extraction kinetics. The use of metallic sodium as the anode not only poses a risk of sodium dendrite growth but also fails to provide sufficient lithium-ion storage sites. Furthermore, the electrolyte in this patent uses a fixed-ratio NASICON structure, which, once determined, cannot be flexibly adjusted according to the active components of the electrodes, resulting in inherent defects such as low lithium-ion conductivity and imbalance in dual-ion transport. Patent CN117638052A discloses a lithium-sodium dual-ion cathode material, which adopts a layered oxide structure with a gradient distribution of (LixNay)NiaCobM1-a-bO2. However, there is still room for improvement in terms of safety and material compatibility.

[0005] In view of this, the present invention is proposed. Summary of the Invention

[0006] The purpose of this invention is to provide a lithium-sodium dual-ion all-solid-state battery and its preparation method, in order to solve the following problems in the prior art: the inability of a single electrode material in lithium-sodium dual-ion batteries to simultaneously adapt to the differentiated intercalation and deintercalation behavior of lithium and sodium dual ions, resulting in insufficient dual-ion storage sites and low capacity utilization; the fixed and unadjustable solid electrolyte ratio, leading to inaccurate matching with electrode active components, low lithium-ion conductivity, and imbalance of dual-ion transport; the lack of continuous ion transport channels between the positive electrode, electrolyte layer, and negative electrode, resulting in high interface impedance and obstructed ion transport; and the problems of poor safety and severe performance degradation at low temperatures in traditional liquid electrolyte systems.

[0007] This invention is implemented as follows: In a first aspect, the present invention provides a lithium-sodium dual-ion all-solid-state battery, which is a layered all-solid-state stacked structure, formed by sequentially bonding and pressing a positive electrode sheet, a lithium-sodium dual-ion mixed solid electrolyte film layer and a negative electrode sheet. The positive electrode sheet includes a positive electrode main material and a first lithium-sodium dual-ion mixed solid electrolyte. The positive electrode main material is a compound of vanadium-based polyanionic sodium salt and vanadium-based polyanionic lithium salt in a mass ratio of 1:1 to 1:5. The negative electrode sheet comprises a negative electrode main material and a second lithium-sodium dual-ion mixed solid electrolyte. The negative electrode main material is a composite of silicon-carbon material and soft carbon material in a mass ratio of 1:1 to 1:5. The first lithium-sodium dual-ion mixed solid electrolyte, the lithium-sodium dual-ion mixed solid electrolyte film layer, and the second lithium-sodium dual-ion mixed solid electrolyte are all mixtures of lithium-ion solid electrolyte and sodium-ion solid electrolyte.

[0008] In an optional embodiment, the vanadium-based polyanionic sodium salt includes one of sodium vanadium phosphate, sodium vanadium pyrophosphate, and sodium vanadium fluorophosphate; The vanadium-based polyanionic lithium salt includes one of lithium vanadium phosphate, lithium vanadium pyrophosphate, and lithium vanadium fluorophosphate.

[0009] In an optional embodiment, the total mass percentage of the positive electrode material in the positive electrode sheet is 50% to 70%, and the mass percentage of the first lithium-sodium dual-ion mixed solid electrolyte is 30% to 50%.

[0010] In an optional embodiment, the total mass percentage of the negative electrode material in the negative electrode sheet is 50% to 70%, and the mass percentage of the second lithium-sodium dual-ion mixed solid electrolyte is 30% to 50%.

[0011] In an optional embodiment, the mass ratio of the lithium-ion solid electrolyte to the sodium-ion solid electrolyte in the lithium-sodium dual-ion mixed solid electrolyte membrane layer is 1:5 to 5:1.

[0012] In an optional embodiment, the positive electrode and / or the negative electrode further comprise a conductive agent and a first binder; the conductive agent is one or more of carbon-based conductive agents SP, VGCF, CNT, and Ketjen Black; the first binder is a polymeric binder.

[0013] In an optional embodiment, the lithium-sodium dual-ion mixed solid electrolyte membrane layer further includes a second binder, wherein the mass percentage of the second binder in the lithium-sodium dual-ion mixed solid electrolyte membrane layer is 1-5%.

[0014] Secondly, the present invention provides a method for preparing a lithium-sodium dual-ion all-solid-state battery as described in the foregoing embodiments, comprising the following steps: S1. Positive electrode preparation: Vanadium-based polyanionic sodium salt and vanadium-based polyanionic lithium salt are mixed to obtain the positive electrode main material. The positive electrode main material, the first lithium sodium dual ion mixed solid electrolyte, the conductive agent and the binder are added to the solvent to make a positive electrode slurry. The positive electrode sheet is obtained by coating, drying and rolling. S2. Preparation of all-solid electrolyte membrane: Lithium-ion solid electrolyte and sodium-ion solid electrolyte are mixed to obtain lithium-sodium dual-ion mixed solid electrolyte. The lithium-sodium dual-ion mixed solid electrolyte and binder are added to a solvent to make an electrolyte slurry. The all-solid electrolyte membrane is obtained by coating, solvent evaporation, curing and peeling. S3. Negative electrode preparation: Silicon-carbon material and soft carbon material are mixed to obtain the negative electrode main material. The negative electrode main material is mixed with a second lithium-sodium dual-ion mixed solid electrolyte, a conductive agent and a binder in a solvent to make a negative electrode slurry. After coating, drying and rolling, a negative electrode sheet is obtained. S4. Battery assembly: The positive electrode, the all-solid electrolyte membrane, and the negative electrode are sequentially bonded together and then packaged to obtain the lithium-sodium dual-ion all-solid-state battery.

[0015] In an optional implementation, step S1 includes preheating drying and vacuum drying; And / or, in step S2, the solvent evaporates at room temperature, and the curing includes vacuum drying at 80~120°C.

[0016] Thirdly, the present invention provides an electrical device comprising a lithium-sodium dual-ion all-solid-state battery as described in the foregoing embodiments.

[0017] The present invention has the following beneficial effects: (1) The vanadium-based dual-material composite positive electrode and carbon-based dual-material composite negative electrode of this application can perfectly adapt to the differentiated insertion and extraction behavior of lithium sodium dual ions. The positive electrode takes into account both high voltage and lattice stability, while the negative electrode provides sufficient dual-ion storage sites and suppresses volume deformation. Compared with traditional single electrode materials, the effective utilization rate of dual ions in this application is increased by 10% to 18%, and the volumetric energy density is increased by more than 15% compared with pure sodium-based all-solid-state batteries, completely solving the defects of dual-ion incompatibility and low capacity of traditional dual-ion batteries.

[0018] (2) This application allows for flexible adjustment of the lithium / sodium solid electrolyte ratio within the range of 1:5 to 5:1, based on the ratio of lithium and sodium active materials in the positive and negative electrodes, to achieve precise matching between the medium and the active materials. Simultaneously, the global dual-ion electrolyte forms a continuous transport network, with lithium ions playing an ion lubricating role, lowering the sodium ion insertion / extraction barrier by 0.02 to 0.04 eV, significantly enhancing the dual-ion synergistic transport capability. The capacity retention rate at -20℃ can reach 77%, and the wide temperature range adaptability is significantly improved.

[0019] (3) Based on the global homogeneous dual-ion electrolyte structure, the solid-solid interface transport barrier is completely eliminated, solving the pain points of lithium-ion conduction obstruction and uneven migration of dual ions in a single electrolyte system, and the interface impedance is greatly reduced.

[0020] (4) The all-solid structure without liquid electrolyte in this application reduces safety risks such as thermal runaway, leakage, and fire, and has extremely strong interface stability under high temperature and high pressure. At the same time, by partially replacing scarce lithium-based materials with sodium-based materials, the lithium resource consumption of the battery is reduced by more than 40%, and the raw material cost is reduced by 20% to 30% compared with the same specification of all-solid-state lithium battery. Under the premise of ensuring high performance and high safety, the production cost is greatly reduced, and the advantages of industrialization are prominent. Attached Figure Description

[0021] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0022] Figure 1 This is a schematic diagram of the structure of the lithium-sodium dual-ion all-solid-state battery provided in Embodiment 1 of the present invention.

[0023] Figure 2 This is an assembly flowchart of the lithium-sodium dual-ion all-solid-state battery provided in Embodiment 1 of the present invention.

[0024] Figure 3 This is an assembly flowchart of the lithium-sodium dual-ion all-solid-state battery provided in Embodiment 2 of the present invention.

[0025] Figure 4 This is a schematic diagram of the battery structure provided by the present invention.

[0026] Figure 5 This is a schematic diagram of the electrical device provided by the present invention. Detailed Implementation

[0027] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0028] In a first aspect, the present invention provides a lithium-sodium dual-ion all-solid-state battery, which is a layered all-solid-state stacked structure, formed by sequentially bonding and pressing a positive electrode sheet, a lithium-sodium dual-ion mixed solid electrolyte film layer and a negative electrode sheet. The positive electrode sheet includes a positive electrode main material and a first lithium-sodium dual-ion mixed solid electrolyte. The positive electrode main material is a compound of vanadium-based polyanionic sodium salt and vanadium-based polyanionic lithium salt in a mass ratio of 1:1 to 1:5. The negative electrode sheet comprises a negative electrode main material and a second lithium-sodium dual-ion mixed solid electrolyte. The negative electrode main material is a composite of silicon-carbon material and soft carbon material in a mass ratio of 1:1 to 1:5. The first lithium-sodium dual-ion mixed solid electrolyte, the lithium-sodium dual-ion mixed solid electrolyte film layer, and the second lithium-sodium dual-ion mixed solid electrolyte are all mixtures of lithium-ion solid electrolyte and sodium-ion solid electrolyte.

[0029] The lithium-sodium dual-ion all-solid-state battery provided by this invention adopts a layered all-solid-state stacked structure. Through the organic combination of a dual-material synergistic electrode system and a globally integrated dual-ion transport network, it systematically solves multiple technical problems in existing technologies, such as poor dual-ion compatibility of single electrode materials, ion transport imbalance caused by a fixed solid electrolyte ratio, and high interfacial impedance. The overall structure of the battery, from the positive electrode side to the negative electrode side, consists of a positive electrode sheet, a lithium-sodium dual-ion mixed solid electrolyte film, and a negative electrode sheet. These three components are tightly bonded together using a hot-pressing process to form an integrated stack. The battery contains no liquid electrolyte or organic solvent.

[0030] The positive electrode uses a blend of vanadium-based polyanionic sodium salt and vanadium-based polyanionic lithium salt as the active material. Both of these vanadium-based phosphate materials belong to the NASICON-type crystal structure and possess three-dimensional open ion transport channels, but their lattice parameters differ significantly. The vanadium-based polyanionic lithium salt (such as Li3V2(PO4)3) has a smaller lattice constant, and its three-dimensional channel size is more closely matched to the ionic radius of lithium ions, which is beneficial for the rapid insertion and extraction of lithium ions. Meanwhile, the vanadium-based polyanionic sodium salt (such as Na3V2(PO4)3), after being expanded by sodium ions, has a larger channel size, which can accommodate the larger ionic radius of sodium ions, providing ample space for stable sodium ion storage. By blending the two in a certain proportion, the positive electrode simultaneously possesses both rapid lithium ion insertion / extraction channels and stable sodium ion storage space. The two ions do not interfere with each other in their respective lattice channels, fundamentally solving the technical challenge that a single positive electrode material cannot simultaneously accommodate two ions with significantly different sizes. Furthermore, the two vanadium-based phosphate materials complement each other in terms of operating voltage: the operating voltage plateau of vanadium-based polyanionic lithium salt is approximately 3.6~4.1V, contributing to the high-voltage characteristics of the cathode; while the plateau of vanadium-based polyanionic sodium salt is approximately 3.0~3.8V, contributing to the low-voltage capacity and stable discharge curve of the cathode. The combined effect results in a smoother discharge curve for the cathode, which is beneficial for voltage monitoring and state-of-charge estimation in the battery management system.

[0031] The negative electrode uses a composite of silicon-carbon and soft carbon materials as the main active material, leveraging the complementary effects of the two carbon-based materials in terms of storage mechanism and mechanical properties to achieve performance optimization. In silicon-carbon materials, the silicon component stores lithium / sodium through an alloying reaction, theoretically achieving a specific capacity of approximately 3500 mAh / g (based on silicon). However, it experiences significant volume expansion (up to 300% or more) during charge and discharge, making the electrode structure prone to cracking and pulverization due to repeated expansion and contraction when used alone. Soft carbon materials are layered amorphous carbon that stores charge through interlayer adsorption, exhibiting minimal volume change and excellent cycle stability, but with a lower specific capacity. By combining the two, the soft carbon component forms a continuous elastic framework network in the electrode, encapsulating and supporting the silicon-carbon particles. This effectively buffers the volume expansion stress of the silicon-carbon during charge and discharge, maintaining the integrity of the electrode structure. Simultaneously, the storage sites within the soft carbon itself provide additional intercalation space for dual ions. The synergistic effect of these two materials allows the composite negative electrode to achieve significantly better cycle stability than pure silicon-carbon negative electrodes while maintaining a high capacity.

[0032] During charging and discharging, the working principle of the lithium-sodium dual-ion all-solid-state battery of this invention is as follows: During charging, lithium ions and sodium ions are extracted from the lattice of the positive electrode active material under the action of an external electric field. They migrate to the interface between the positive electrode and the electrolyte film through the dual-ion mixed solid electrolyte conduction network inside the positive electrode sheet, then pass through the electrolyte film to the negative electrode side, and are then embedded into the negative electrode active material through the mixed solid electrolyte conduction network inside the negative electrode sheet. During discharging, lithium ions and sodium ions are extracted from the negative electrode active material, pass through the electrolyte film along the opposite path, and are re-embedded into the lattice of the positive electrode active material. In this process, lithium ions, due to their small ionic radius and fast migration rate, act as ion lubricants in the mixed solid electrolyte. The local electric field and concentration gradient formed by their rapid migration help to reduce the insertion / extraction energy barrier of sodium ions, thus significantly improving the transport rate of sodium ions and achieving synergistic and efficient transport of lithium and sodium dual ions. This working mechanism is fundamentally different from that of traditional single-ion batteries.

[0033] The lithium-sodium dual-ion hybrid solid electrolyte membrane and the electrolyte embedded within the positive and negative electrodes are both physically mixed using independent lithium-ion solid electrolytes and sodium-ion solid electrolytes in a specific ratio. This physical mixing method differs from the chemical synthesis approach that simultaneously introduces lithium and sodium ions into the same crystal lattice. Its core advantage lies in the fact that the lithium-ion and sodium-ion solid electrolytes can each independently select their optimal material systems and ratios without interfering with each other. The resulting hybrid electrolyte, obtained through physical mixing, possesses the conductivity of both lithium and sodium ions. More importantly, the lithium-ion and sodium-ion solid electrolytes use the exact same type and ratio in the three regions of the positive electrode, electrolyte membrane, and negative electrode, ensuring the homogeneity and continuity of the ion conduction system across these three regions and eliminating interfacial transport barriers that may arise due to differences in electrolyte type or composition.

[0034] The lithium-ion and sodium-ion solid electrolytes mentioned above can all be conventional commercially available lithium-ion and sodium-ion solid electrolytes.

[0035] In an optional embodiment, the vanadium-based polyanionic sodium salt includes one of sodium vanadium phosphate, sodium vanadium pyrophosphate, and sodium vanadium fluorophosphate.

[0036] In an optional embodiment, the vanadium-based polyanionic lithium salt includes one of lithium vanadium phosphate, lithium vanadium pyrophosphate, and lithium vanadium fluorophosphate.

[0037] In an optional embodiment, the lithium-ion solid electrolyte and sodium-ion solid electrolyte used in the first lithium-sodium dual-ion mixed solid electrolyte, the lithium-sodium dual-ion mixed solid electrolyte membrane layer, and the second lithium-sodium dual-ion mixed solid electrolyte are all of the same type and ratio.

[0038] In an optional embodiment, the lithium-ion solid electrolyte includes at least one of sulfide-based, oxide-based, and halide-based lithium-ion solid electrolytes.

[0039] In an optional embodiment, the sodium-ion solid electrolyte includes at least one of sulfide-based, oxide-based, and halide-based sodium-ion solid electrolytes.

[0040] Furthermore, the lithium-ion solid electrolyte is Li6PS5Cl.

[0041] Furthermore, the sodium ion solid electrolyte is Na6PS5Cl.

[0042] In an optional embodiment, the mass ratio of the vanadium-based polyanionic sodium salt to the vanadium-based polyanionic lithium salt can be selected from 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, or any range between the two.

[0043] In an optional embodiment, the total mass percentage of the positive electrode material in the positive electrode sheet is 50% to 70%, and the mass percentage of the first lithium-sodium dual-ion mixed solid electrolyte is 30% to 50%.

[0044] In an optional embodiment, the positive electrode further comprises a conductive agent and a first binder; the conductive agent is a carbon-based conductive agent; and the first binder is a polymeric binder.

[0045] Furthermore, the carbon-based conductive agent includes one or more of the following: SP, VGCF, CNT, and Ketjen Black.

[0046] Furthermore, the first adhesive comprises one or more of PVDF, PTFE, SEBS, and HNBR.

[0047] In this invention, the active material of the positive electrode is a composite of vanadium-based polyanionic sodium salt and vanadium-based polyanionic lithium salt. The mass ratio of the two is adjustable within the range of 1:1 to 1:5. Under this ratio, the lattice complementarity effect of the positive electrode achieves a better balance, which can ensure the rapid insertion and extraction of lithium ions to provide a high voltage platform and high capacity, while also providing sufficient and stable storage space for sodium ions. When the proportion of vanadium-based polyanionic sodium salt is too high, there are too many sodium ion channels and not enough lithium ion channels, resulting in a decrease in the battery's operating voltage platform and impaired rate performance. When the proportion of vanadium-based polyanionic lithium salt is too high, the sodium ion storage space is limited, the amount of sodium ion insertion is reduced, and the synergistic effect of the two ions cannot be fully utilized.

[0048] In addition to the active material, the positive electrode also includes a first lithium-sodium dual-ion mixed solid electrolyte, a conductive agent, and a binder. The first lithium-sodium dual-ion mixed solid electrolyte is a physical mixture of lithium-ion solid electrolyte and sodium-ion solid electrolyte in a target ratio, accounting for 30%–50% of the positive electrode by mass. The ion conduction network formed by the electrolyte within the positive electrode penetrates between the active material particles, allowing lithium and sodium ions stored in the active material to migrate efficiently to the electrolyte membrane layer and then across the membrane layer to the opposite electrode. The conductive agent is a carbon-based conductive agent, typically used in the positive electrode at 2%–5% of the total mass. Its function is to establish efficient electron conduction pathways between the active material particles and between the active material and the current collector. The binder is one or a combination of two polymeric binders, typically used in the positive electrode at 1%–3% of the total mass. Its function is to bond the active material, electrolyte, and conductive agent particles together and adhere them to the surface of the current collector. It should be noted that the introduction of the dual-ion mixed solid electrolyte into the positive electrode can be achieved by directly adding the pre-mixed solid electrolyte powder and active material together to a solvent for slurry preparation, or by first pre-dispersing the solid electrolyte powder in a solvent to form an electrolyte slurry before mixing it with the active material. Both methods can achieve uniform distribution of the electrolyte within the positive electrode. Positive electrodes prepared using this method exhibit a uniformly distributed three-dimensional interpenetrating structure between the internal dual-ion solid electrolyte network and the active material particles, which facilitates rapid ion transport within the electrode.

[0049] In an optional embodiment, the total mass percentage of the negative electrode material in the negative electrode sheet is 50% to 70%, and the mass percentage of the second lithium-sodium dual-ion mixed solid electrolyte is 30% to 50%.

[0050] In an optional embodiment, the negative electrode sheet further comprises a conductive agent and a second binder; the conductive agent is a carbon-based conductive agent; and the second binder is a polymeric binder.

[0051] In an optional embodiment, the polymeric adhesive includes one or more of PVDF, PTFE, SEBS, and HNBR.

[0052] Furthermore, the carbon-based conductive agent includes one or more of the following: SP, VGCF, CNT, and Ketjen Black.

[0053] In this invention, the active material of the negative electrode is a composite of silicon-carbon and soft carbon materials. The silicon-carbon material is a composite material formed by uniformly dispersing nano- or submicron silicon particles in a carbon matrix, with a silicon content typically between 20% and 60%. The carbon matrix can be graphite, amorphous carbon, or a composite of both. The role of the carbon matrix is ​​to buffer the volume expansion of silicon particles and provide additional electron conduction pathways. The soft carbon material refers to carbon materials that retain their amorphous layered structure after being treated at high temperatures (typically 1000–1600°C), such as petroleum coke, needle coke, and carbon microspheres. Its interlayer spacing is slightly larger than that of graphite, which is beneficial for ion interlayer insertion and extraction. The mass ratio of silicon-carbon to soft carbon material is adjustable within the range of 1:1 to 1:5. Within this preferred range, the elastic framework of soft carbon can effectively buffer the volume expansion stress of silicon-carbon during charging and discharging, while the charging sites of soft carbon provide additional insertion space for dual ions, thus balancing the high capacity and long-cycle stability of the negative electrode. When the proportion of soft carbon is too low, the buffering effect is insufficient; when the proportion of soft carbon is too high, the overall capacity of the negative electrode decreases significantly. By adjusting the ratio of silicon-carbon to soft carbon, the specific capacity of the negative electrode can be flexibly designed within the range of 200~500 mAh / g to match the needs of different positive electrode capacities and different lithium-sodium ratios. For example, when the positive electrode uses a high lithium ratio (vanadium-based polyanionic sodium salt: vanadium-based polyanionic lithium salt = 1:5), the proportion of silicon-carbon in the negative electrode can be appropriately increased to match the high capacity output of the positive electrode; when the positive electrode uses a high sodium ratio (vanadium-based polyanionic sodium salt: vanadium-based polyanionic lithium salt = 1:1), the proportion of silicon-carbon in the negative electrode can be appropriately reduced to improve cycle stability.

[0054] The negative electrode also contains a second lithium-sodium dual-ion mixed solid electrolyte, a conductive agent, and a binder. The second lithium-sodium dual-ion mixed solid electrolyte uses the exact same lithium-ion solid electrolyte type, sodium-ion solid electrolyte type, and ratio as the first lithium-sodium dual-ion mixed solid electrolyte used in the positive electrode and the mixed electrolyte used in the electrolyte membrane layer. This ensures that the electrolyte composition is consistent and its properties are continuous throughout the entire ion transport path from the positive to the negative electrode, eliminating interfacial ion transport resistance due to differences in electrolyte type or ratio. The second lithium-sodium dual-ion mixed solid electrolyte accounts for 30% to 50% of the mass of the negative electrode. The types of conductive agent and binder are consistent with those of the positive electrode.

[0055] In an optional embodiment, the mass ratio of the lithium-ion solid electrolyte to the sodium-ion solid electrolyte in the lithium-sodium dual-ion mixed solid electrolyte membrane layer is 1:5 to 5:1.

[0056] Furthermore, the mass ratio of the lithium-ion solid electrolyte to the sodium-ion solid electrolyte can be selected from 1:5, 1:4, 1:3, 1:2, 1:1, 2:1, 3:1, 4:1, 5:1, or any range between the two.

[0057] In an optional embodiment, the lithium-sodium dual-ion mixed solid electrolyte membrane layer further includes a second binder, wherein the mass percentage of the second binder in the lithium-sodium dual-ion mixed solid electrolyte membrane layer is 1-5%.

[0058] In this invention, the lithium-sodium dual-ion hybrid solid electrolyte membrane is one of the core components of the battery. Its function is to simultaneously conduct lithium ions and sodium ions between the positive and negative electrodes, and to provide electronic insulation to prevent short circuits between the positive and negative electrodes. Unlike the porous membranes used in liquid batteries, the all-solid-state electrolyte membrane of this invention is a dense ion-conducting medium, without the porous structure filled by liquid electrolytes. Therefore, it physically eliminates the risk of short circuits caused by lithium or sodium dendrites penetrating the membrane, which is one of the core safety advantages of all-solid-state batteries compared to liquid batteries. This membrane is prepared by uniformly mixing the lithium-sodium dual-ion hybrid solid electrolyte with a binder, followed by coating, solvent evaporation, curing, and peeling, resulting in a dense and flexible membrane structure.

[0059] In lithium-sodium dual-ion hybrid solid electrolytes, the selection of lithium-ion solid electrolytes and sodium-ion solid electrolytes requires comprehensive consideration of factors such as ionic conductivity, electrochemical stability window, chemical compatibility with electrode materials, and mechanical properties. The mass ratio of lithium-ion solid electrolyte to sodium-ion solid electrolyte is adjustable within the range of 1:5 to 5:1, and the specific ratio is flexibly adjusted according to the proportion of lithium and sodium active components in the positive and negative electrode active materials. Generally speaking, when the proportion of vanadium-based polyanionic lithium salt in the positive electrode is high and the proportion of high-capacity silicon-carbon in the negative electrode is high, the proportion of lithium-ion solid electrolyte should be appropriately increased to enhance the lithium-ion conduction efficiency; conversely, the proportion of sodium-ion solid electrolyte should be appropriately increased.

[0060] In the process of lithium-ion and sodium-ion co-transport, lithium ions, due to their smaller ionic radius and higher migration rate, act as ion lubricants in the mixed electrolyte. Specifically, the diffusion coefficient of lithium ions in the mixed solid electrolyte is typically 1 to 2 orders of magnitude higher than that of sodium ions. The rapid migration of lithium ions can create a local electric field and concentration gradient within the solid electrolyte, effectively reducing the sodium ion insertion / extraction barrier by approximately 0.02 to 0.04 eV, thereby significantly promoting the charge transfer reaction kinetics of sodium ions at the electrode / electrolyte interface. This lithium-sodium dual-ion synergistic transport mechanism significantly improves the overall dual-ion transport efficiency of the mixed electrolyte compared to a single-ion electrolyte system.

[0061] This invention does not impose any particular limitation on the shape of the battery; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 4 This is a square-structured battery as an example. It is understood that the arrangement of the terminals (or electrode terminals) is not limited to the same-side positive and negative terminals shown in the figure, and they can also be arranged at two opposite ends of the battery. This invention does not limit this arrangement.

[0062] In some embodiments, the battery includes a casing, within which electrode assemblies are encapsulated. The battery may contain one or more electrode assemblies, which can be selected by those skilled in the art according to specific practical needs.

[0063] Secondly, the present invention provides a method for preparing a lithium-sodium dual-ion all-solid-state battery as described in the foregoing embodiments, comprising the following steps: S1. Positive electrode preparation: Vanadium-based polyanionic sodium salt and vanadium-based polyanionic lithium salt are mixed to obtain the positive electrode main material. The positive electrode main material, the first lithium sodium dual ion mixed solid electrolyte, the conductive agent and the binder are added to the solvent to make a positive electrode slurry. The positive electrode sheet is obtained by coating, drying and rolling. S2. Preparation of all-solid electrolyte membrane: Lithium-ion solid electrolyte and sodium-ion solid electrolyte are mixed to obtain lithium-sodium dual-ion mixed solid electrolyte. The lithium-sodium dual-ion mixed solid electrolyte and binder are added to a solvent to make an electrolyte slurry. The all-solid electrolyte membrane is obtained by coating, solvent evaporation, curing and peeling. S3. Negative electrode preparation: Silicon-carbon material and soft carbon material are mixed to obtain the negative electrode main material. The negative electrode main material is mixed with a second lithium-sodium dual-ion mixed solid electrolyte, a conductive agent and a binder in a solvent to make a negative electrode slurry. After coating, drying and rolling, a negative electrode sheet is obtained. S4. Battery assembly: The positive electrode, the all-solid electrolyte membrane, and the negative electrode are sequentially bonded together and then packaged to obtain the lithium-sodium dual-ion all-solid-state battery.

[0064] The specific methods for preparing the positive electrode include: Weigh the positive electrode active material, dual-ion mixed solid electrolyte, conductive agent, and binder according to the specified ratio, and add them to an appropriate amount of organic solvent (such as butyl butyrate, N-methylpyrrolidone, etc.). Stir the mixture in a high-speed dispersion device at a speed of 1500~2500 rpm for 3~6 hours to ensure that all components are fully dispersed and uniformly mixed to obtain a positive electrode slurry. Transfer the slurry to a coating machine and coat it uniformly onto the surface of an aluminum current collector with a thickness of 12~20 μm. After coating, the electrode sheet is first preheated and dried at 80~100℃ to remove most of the surface solvent, and then transferred to a vacuum drying oven at 110~130℃ for 8~15 hours to completely remove residual moisture and solvent. The dried electrode sheet is then compacted by a roller press to the target porosity and thickness to obtain a positive electrode sheet that meets the requirements. Throughout the entire preparation process, the slurry preparation, coating, drying, and rolling are all carried out in a dry environment with a dew point not higher than -60℃ to avoid side reactions between moisture and the solid electrolyte material that would lead to a decrease in ionic conductivity.

[0065] The preparation process of the electrolyte membrane layer specifically includes: The selected ratio of lithium-ion solid electrolyte and sodium-ion solid electrolyte is mixed evenly. The mixing methods for lithium-ion solid electrolyte and sodium-ion solid electrolyte can include ball milling, high-speed stirring, or air jet milling. The ball milling speed is 200-500 rpm, and the milling time is 2-8 hours. After uniform mixing, a binder is added, with the preferred electrolyte-to-binder mass ratio being 98:2. An organic solvent is added to the mixture, and the mixture is stirred at 1500-2500 rpm for 5-8 hours in a high-speed stirring device until a uniform electrolyte slurry is formed. The slurry is then evenly coated onto the surface of a substrate such as polytetrafluoroethylene or release paper using a coating machine, controlling the coating thickness to ensure that the final dried film thickness is within the range of 30-80 μm. The mixture is first allowed to stand at room temperature for 30-60 minutes to allow the surface solvent to evaporate naturally, and then transferred to a vacuum drying oven at 80-120℃ for 6-12 hours to ensure complete solvent removal. After cooling to room temperature, the membrane is carefully peeled off from the substrate to obtain a flexible, dense, and pore-free all-solid electrolyte membrane.

[0066] The specific process of preparing the negative electrode includes: Silicon-carbon material and soft carbon material are mixed uniformly according to a certain ratio to obtain the negative electrode active material. The negative electrode active material, dual-ion mixed solid electrolyte, conductive agent, and binder are weighed according to the ratio and added to an appropriate amount of organic solvent. The mixture is stirred in a high-speed dispersion device at 1500-2500 rpm for 3-6 hours to ensure thorough dispersion of the components, obtaining a uniform negative electrode slurry. The slurry is coated onto the surface of a copper current collector with a thickness of 8-12 μm, preheated at 80-100℃, vacuum dried at 110-130℃ for 8-15 hours, and then roller-pressed to the target thickness and porosity to obtain the negative electrode sheet. Slurry preparation and subsequent processes are all carried out in a dry environment with a dew point not exceeding -60℃.

[0067] Battery assembly specifically includes: The prepared positive electrode, all-solid electrolyte membrane, and negative electrode are precisely aligned sequentially and then placed in a hot-pressing mold. During the hot-pressing process, the electrolyte membrane and the positive and negative electrodes form a tight solid-solid contact interface under the combined action of temperature and pressure, minimizing the contact resistance at the interface. After hot pressing, the cells are naturally cooled to room temperature to obtain a well-encapsulated lithium-sodium dual-ion all-solid-state single cell. All assembly operations are performed in a dry environment with a dew point not exceeding -60°C to avoid the introduction of moisture. After battery encapsulation, formation and aging treatments can be performed according to actual application requirements. Only after formation and aging treatments can the battery undergo subsequent performance testing and use.

[0068] In an optional embodiment, the drying in step S1 includes preheating drying at 80°C and vacuum drying at 120°C.

[0069] In an optional embodiment, the solvent evaporation temperature in step S2 is room temperature, and the curing includes vacuum drying at 80~120°C.

[0070] Thirdly, the present invention provides an electrical device, characterized in that it includes a lithium-sodium dual-ion all-solid-state battery as described in the foregoing embodiments. The all-solid-state battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (typically mobile phones, laptops, etc.), electric vehicles (typically pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships, satellites, or energy storage systems, etc.

[0071] Figure 5 This is an example of an electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery for this device, a battery pack or battery module can be used.

[0072] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0073] Example 1 This embodiment provides a lithium-sodium dual-ion all-solid-state battery, the structure of which is as follows: Figure 1 As shown, this is a layered, all-solid-state stacked structure, consisting of a positive electrode sheet, a lithium-sodium dual-ion mixed solid electrolyte film layer, and a negative electrode sheet sequentially bonded and hot-pressed together. In this embodiment, the positive electrode material Na3V2(PO4)3 to Li3V2(PO4)3 mass ratio is 1:3, and the negative electrode material silicon-carbon to soft carbon mass ratio is 1:1. Figure 2As shown, the preparation method includes the following steps: (1) Preparation of positive electrode: The positive electrode composition was prepared with 70% active main material and 30% first lithium sodium dual-ion mixed solid electrolyte (Li6PS5Cl and Na6PS5Cl in a ratio of 2:5). The active main material, vanadium-based polyanionic sodium salt and vanadium-based polyanionic lithium salt, were uniformly mixed at a mass ratio of 1:3. The above positive electrode main material, dual-ion solid electrolyte, VGCF, and SEBS were added to butyl butyrate solvent in proportion and stirred at high speed for 4 h to prepare a uniform and stable positive electrode slurry. The slurry was uniformly coated on the surface of aluminum current collector, preheated and dried at 80°C to remove the surface solvent, and then vacuum dried at 120°C for 12 h to completely remove water. Finally, it was rolled and compacted to obtain a flat and dense positive electrode sheet. The electrode sheet preparation and battery assembly steps were all carried out in a -60°C dry room.

[0074] (2) Preparation of all-solid electrolyte layer A lithium-sodium dual-ion mixed solid electrolyte (Li6PS5Cl and Na6PS5Cl 2:5) was uniformly mixed with SEBS binder at a mass ratio of 98:2. Anisole solvent was added and stirred at high speed for 6 h to prepare a uniform electrolyte slurry. The slurry was uniformly coated on the surface of the substrate, and after the surface solvent was evaporated at room temperature, it was vacuum dried at 100℃ for 8 h. After cooling, the substrate was peeled off to obtain a flexible, dense, and pore-free all-solid electrolyte film.

[0075] (3) Preparation of negative electrode The negative electrode composition is prepared by mixing 70% active main material and 30% second lithium sodium dual-ion mixed solid electrolyte (Li6PS5Cl and Na6PS5Cl in a 2:5 ratio). The active main material is a uniform mixture of silicon carbon material and soft carbon material in a 1:1 mass ratio. The above negative electrode main material, dual-ion solid electrolyte, VGCF, and HNBR are added to p-xylene solvent in proportion and stirred at high speed for 4 hours to prepare a uniform negative electrode slurry. This slurry is then uniformly coated onto the surface of a copper current collector, preheated to 80°C, vacuum dried at 120°C for 12 hours, and then rolled to obtain the negative electrode sheet.

[0076] (4) Battery assembly After the prepared negative electrode sheet is precisely aligned and bonded with the all-solid electrolyte membrane layer, it is then stacked and composited with the positive electrode sheet. The whole assembly is then compacted and packaged using a hot-pressing process, and finally a lithium-sodium dual-ion all-solid-state single cell battery is prepared.

[0077] Electrochemical performance tests were conducted on the lithium-sodium dual-ion all-solid-state battery prepared in this embodiment: At 60℃ and 1C rate, the discharge specific capacity was 145 mAh / g; after 800 cycles at 1C rate, the capacity retention was 82.3%; and at -20℃, the capacity retention reached 61.5%. The positive and negative electrode materials in this embodiment have a balanced ratio, and the synergistic effect of the dual-material composite is good. The composite positive electrode can simultaneously adapt to the intercalation and deintercalation behavior of lithium and sodium dual ions, while the composite negative electrode can stably provide sufficient dual-ion charge storage sites. The globally integrated dual-ion electrolyte transport network has good connectivity, resulting in balanced overall battery performance. The 82.3% capacity retention after 800 cycles indicates that the soft carbon framework in the composite negative electrode effectively buffers the volume expansion of silicon and carbon, and the electrode structure maintains good integrity during long-term cycling.

[0078] Example 2 This embodiment provides a lithium-sodium dual-ion all-solid-state battery, and the specific preparation method is as follows: Figure 3 As shown, specifically: (1) Positive electrode preparation: The total components of the positive electrode are prepared according to the ratio of 70% active main material and 30% first lithium sodium dual-ion mixed solid electrolyte. The active main material is formed by uniformly mixing Na3V2(PO4)3 and Li3V2(PO4)3 at a mass ratio of 1:3, and the first lithium sodium dual-ion mixed solid electrolyte is formed by mixing Li6PS5Cl and Na6PS5Cl at a mass ratio of 2:5. The above positive electrode main material, dual-ion mixed solid electrolyte, VGCF and SEBS are added to butyl butyrate solvent in proportion and stirred at 2000 rpm for 4 hours in a high-speed stirring device to prepare a uniform and stable positive electrode slurry. The slurry is uniformly coated on the surface of aluminum current collector by a coating machine. It is first preheated and dried at 80℃, then vacuum dried at 120℃ for 12 hours, and finally compacted by a roller press to obtain the positive electrode sheet.

[0079] (2) Preparation of all-solid electrolyte membrane: A lithium-sodium dual-ion mixed solid electrolyte was obtained by uniformly mixing Li6PS5Cl and Na6PS5Cl at a mass ratio of 2:5. This mixed solid electrolyte was then uniformly mixed with SEBS binder at a mass ratio of 98:2. After adding anisole solvent, the mixture was stirred at 2000 rpm for 6 hours in a high-speed mixer to obtain a uniform electrolyte slurry. The slurry was then uniformly coated onto the surface of a substrate using a coating machine. The surface solvent was first allowed to evaporate naturally at room temperature, and then vacuum dried at 100℃ for 8 hours. After cooling, the slurry was peeled off from the substrate to obtain a flexible, dense, and non-porous all-solid electrolyte film.

[0080] (3) Anode preparation: The negative electrode composition was prepared by mixing 70% active material and 30% second lithium-sodium dual-ion mixed solid electrolyte (Li6PS5Cl to Na6PS5Cl ratio 2:5). The active material was a uniform mixture of silicon-carbon material and soft carbon material at a mass ratio of 1:1. The negative electrode material, dual-ion mixed solid electrolyte, VGCF, and SEBS were added to p-xylene solvent in proportion and stirred at high speed for 4 hours to prepare a uniform negative electrode slurry. The slurry was coated onto the surface of a copper current collector, preheated to 80℃ and dried under vacuum at 120℃ for 12 hours, then rolled and compacted to obtain the negative electrode sheet.

[0081] (4) Battery assembly: After precisely aligning and bonding the positive electrode sheet with the all-solid electrolyte membrane layer, it is then stacked and composited with the negative electrode sheet. The entire assembly is then compacted and encapsulated using a hot-pressing process, ultimately producing a lithium-sodium dual-ion all-solid-state single cell battery.

[0082] Electrochemical performance tests were conducted on the lithium-sodium dual-ion all-solid-state battery prepared in this embodiment: At 60°C and 1C rate, the discharge specific capacity was 143 mAh / g; after 800 cycles at 1C rate, the capacity retention was 85.1%; and at -20°C, the capacity retention was 59.1%. The overall performance of this embodiment is comparable to that of Example 1, but the capacity retention after 800 cycles is slightly improved, indicating... Figure 3 The optimized assembly process shown improves the solid-solid interface contact quality between the electrode and electrolyte membrane, thereby enhancing the long-cycle stability of the battery. This embodiment also illustrates that in all-solid-state batteries, interface contact quality is one of the key factors affecting battery performance, and process optimization can further improve the battery's cycle stability without altering the material system.

[0083] Example 3 This embodiment provides a lithium-sodium dual-ion all-solid-state battery with a low sodium-to-high lithium ratio, and the specific preparation method is as follows: (1) Preparation of positive electrode: The positive electrode composition is prepared with 70% active material and 30% first lithium-sodium dual-ion mixed solid electrolyte. The active material is a mixture of Na3V2(PO4)3 and Li3V2(PO4)3 at a mass ratio of 1:5, which significantly increases the proportion of lithium-based active material to obtain higher operating voltage and storage capacity. The first lithium-sodium dual-ion mixed solid electrolyte is a mixture of Li6PS5Cl and Na6PS5Cl at a ratio of 1:1 to match the ion transport requirements of the high-lithium active material. The above positive electrode material, dual-ion mixed solid electrolyte, VGCF, and SEBS are added to butyl butyrate solvent in proportion and stirred at 2000 rpm for 4 hours in a high-speed stirrer to prepare a uniform and stable positive electrode slurry. The slurry is uniformly coated onto the surface of an aluminum current collector using a coating machine. It is first preheated and dried at 80℃, then vacuum dried at 120℃ for 12 hours, and finally compacted by a roller press to obtain the positive electrode sheet.

[0084] (2) Preparation of all-solid electrolyte membrane: Li6PS5Cl and Na6PS5Cl were uniformly mixed at a mass ratio of 1:1 to obtain a lithium-sodium dual-ion mixed solid electrolyte, maintaining the same electrolyte ratio as the positive and negative electrodes. This mixed solid electrolyte was then uniformly mixed with SEBS binder at a mass ratio of 98:2. After adding anisole solvent, the mixture was stirred at 2000 rpm for 6 hours in a high-speed mixer to obtain a homogeneous electrolyte slurry. The slurry was then uniformly coated onto the substrate surface using a coating machine. The surface solvent was first allowed to evaporate naturally at room temperature, followed by vacuum drying at 100℃ for 8 hours. After cooling, the slurry was peeled off from the substrate to obtain an all-solid-state electrolyte film.

[0085] (3) Anode preparation: The negative electrode composition is prepared by mixing 70% active main material and 30% secondary lithium-sodium dual-ion mixed solid electrolyte (Li6PS5Cl and Na6PS5Cl in a 1:1 mass ratio). The active main material is a mixture of silicon-carbon and soft carbon materials in a 1.5:1 mass ratio. The secondary lithium-sodium dual-ion mixed solid electrolyte is a mixture of lithium-ion solid electrolyte and sodium-ion solid electrolyte in a 1:1 mass ratio. The above-mentioned negative electrode main material, dual-ion mixed solid electrolyte, VGCF, and SEBS are added to p-xylene solvent in proportion, and stirred at high speed for 4 hours to prepare a uniform negative electrode slurry. The slurry is coated on the surface of a copper current collector, preheated and dried at 80°C, vacuum dried at 120°C for 12 hours, and then rolled and compacted to obtain the negative electrode sheet.

[0086] (4) Battery assembly After the prepared negative electrode sheet is precisely aligned and bonded with the all-solid electrolyte membrane layer, it is then stacked and composited with the positive electrode sheet. The whole assembly is then compacted and packaged using a hot-pressing process, and finally a lithium-sodium dual-ion all-solid-state single cell battery is prepared.

[0087] Electrochemical performance tests were conducted on the lithium-sodium dual-ion all-solid-state battery prepared in this embodiment: At 60°C and 1C rate, the discharge specific capacity was 152 mAh / g; after 800 cycles at 1C rate, the capacity retention was 88.6%; and at -20°C, the capacity retention was 77.2%. This embodiment uses a low-sodium, high-lithium main material ratio. The high proportion of vanadium-based polyanionic lithium salt active material and silicon-carbon material gives the battery a higher operating voltage and storage capacity, with a discharge specific capacity increase of approximately 4.8% compared to Example 1. Adjusting the dual-ion electrolyte ratio from 2:5 to 1:1 increases the proportion of lithium-ion solid electrolyte, significantly improving lithium-ion conductivity and enhancing the ion lubrication effect, thus promoting the synergistic transport of sodium ions. The 800-cycle capacity retention of 88.6% and the -20°C capacity retention of 77.2% are the best values ​​among the four embodiments, indicating that the cycle stability and low-temperature adaptability of the battery are comprehensively improved under the low-sodium, high-lithium ratio.

[0088] Example 4 This embodiment provides a lithium-sodium dual-ion all-solid-state battery with the same sodium-lithium ratio, and the specific preparation method is as follows: (1) Preparation of positive electrode: The positive electrode composition is prepared with 70% active main material and 30% first lithium-sodium dual-ion mixed solid electrolyte. The active main material is a 1:1 mass mixture of Na3V2(PO4)3 and Li3V2(PO4)3. The first lithium-sodium dual-ion mixed solid electrolyte is a 1:1 mixture of Li6PS5Cl and Na6PS5Cl. The above positive electrode main material, dual-ion mixed solid electrolyte, VGCF, and SEBS are added to butyl butyrate solvent in proportion and stirred at 2000 rpm for 4 hours in a high-speed stirrer to prepare a uniform and stable positive electrode slurry. The slurry is uniformly coated onto the surface of an aluminum current collector using a coating machine. It is first preheated and dried at 80℃, then vacuum dried at 120℃ for 12 hours, and finally compacted by a roller press to obtain the positive electrode sheet.

[0089] (2) Preparation of all-solid electrolyte membrane: Li6PS5Cl and Na6PS5Cl were uniformly mixed at a mass ratio of 1:1 to obtain a lithium-sodium dual-ion mixed solid electrolyte, maintaining the same electrolyte ratio as the positive and negative electrodes. This mixed solid electrolyte was then uniformly mixed with SEBS binder at a mass ratio of 98:2. After adding anisole solvent, the mixture was stirred at 2000 rpm for 6 hours in a high-speed mixer to obtain a homogeneous electrolyte slurry. The slurry was then uniformly coated onto the substrate surface using a coating machine. The surface solvent was first allowed to evaporate naturally at room temperature, followed by vacuum drying at 100℃ for 8 hours. After cooling, the slurry was peeled off from the substrate to obtain an all-solid-state electrolyte film.

[0090] (3) Anode preparation: The negative electrode composition was prepared by mixing 70% active main material and 30% secondary lithium-sodium dual-ion mixed solid electrolyte (Li6PS5Cl and Na6PS5Cl in a 1:1 mass ratio). The active main material was a 1:1 mass mixture of silicon-carbon and soft carbon materials. The secondary lithium-sodium dual-ion mixed solid electrolyte was a 1:1 mass mixture of lithium-ion solid electrolyte and sodium-ion solid electrolyte. The above-mentioned negative electrode main material, dual-ion mixed solid electrolyte, VGCF, and SEBS were added to p-xylene solvent in proportion and stirred at high speed for 4 hours to prepare a uniform negative electrode slurry. The slurry was coated on the surface of a copper current collector, preheated and dried at 80°C, vacuum dried at 120°C for 12 hours, and then rolled and compacted to obtain the negative electrode sheet.

[0091] (4) Battery assembly After the prepared negative electrode sheet is precisely aligned and bonded with the all-solid electrolyte membrane layer, it is then stacked and composited with the positive electrode sheet. The whole assembly is then compacted and packaged using a hot-pressing process, and finally a lithium-sodium dual-ion all-solid-state single cell battery is prepared.

[0092] The electrochemical performance of the lithium-sodium dual-ion all-solid-state battery prepared in this embodiment was tested: the discharge specific capacity was 131 mAh / g at 60℃ and 1C rate; the capacity retention rate was 76.9% after 800 cycles at 1C rate; and the capacity retention rate was 79.5% at -20℃.

[0093] Comparative Example 1 This comparative example is basically the same as Example 1, except that soft carbon is used for the negative electrode.

[0094] Electrochemical performance tests were conducted on the lithium-sodium dual-ion all-solid-state battery prepared in this control system: at 60℃ and 1C rate, the discharge specific capacity was 112 mAh / g; after 800 cycles at 1C rate, the capacity retention rate reached 91.7%; and at a low temperature of -20℃, the battery capacity retention rate was 82.7%. The anode material in this system is made entirely of soft carbon, without any silicon-carbon doping. The layered carbon skeleton structure of soft carbon is stable, with minimal volume deformation during charge and discharge, and almost no problem of active material pulverization and shedding. However, soft carbon lacks lithium storage sites, making it difficult to simultaneously and efficiently accommodate lithium and sodium dual ions, thus limiting the overall charge storage capacity. The discharge specific capacity decreased by approximately 22.8% compared to Example 1 (a balanced ratio system of silicon-carbon / soft carbon composite anode). The smooth conduction of dual ions is ensured by the full-domain lithium-sodium dual-ion mixed solid-state electrolyte system. Furthermore, the excellent electronic conductivity and lower solid-solid interface impedance of soft carbon result in slow electrode polarization growth during long cycles. The capacity retention rate of 91.7% after 800 cycles and the capacity retention rate of 82.7% at -20℃ are both better than the low sodium and high lithium ratio experimental group, proving that the pure soft carbon anode system has stronger structural stability and better low-temperature sodium ion migration kinetics; however, it is limited by the low total storage capacity and insufficient high-rate discharge performance, making it difficult to meet the needs of high energy density applications.

[0095] Comparative Example 2 This comparative example is basically the same as Example 1, except that silicon-carbon is used for the negative electrode.

[0096] Electrochemical performance tests were conducted on the lithium-sodium dual-ion all-solid-state battery prepared in this comparative example: at 25°C and 1C rate, the discharge specific capacity was 156 mAh / g; after 800 cycles at 1C rate, the capacity retention was 83.1%; and at -20°C, the capacity retention was 74.3%. The anode was entirely made of silicon-carbon material, with abundant dual-ion alloying storage sites and the strongest storage capacity, resulting in a discharge specific capacity improvement of approximately 7.6% compared to Example 1. However, the pure silicon-carbon sodium-lithium intercalation resulted in significant volume deformation, easily causing particle pulverization, conductive network breakage, and repeated SEI reconstruction, leading to severe long-cycle degradation and poor low-temperature kinetic performance. This demonstrates that a single silicon-carbon anode cannot simultaneously achieve both cycle and low-temperature performance, highlighting the significant technical necessity and innovation of the silicon-carbon / soft carbon composite system of this invention.

[0097] Based on the test results of the above embodiments, this invention effectively solves the core problem that traditional single electrode materials cannot simultaneously adapt to the differentiated intercalation and deintercalation behaviors of lithium and sodium ions through a dedicated synergistic electrode system of vanadium-based polyanionic sodium salt and vanadium-based polyanionic lithium salt composite positive electrode and silicon-carbon and soft carbon composite negative electrode. The reversible dual-ion charge storage utilization rate and electrode structural stability are significantly improved. Through an adjustable system of independent lithium-ion solid electrolyte and sodium-ion solid electrolyte composite, and a globally homogeneous integrated design of the positive electrode-electrolyte layer-negative electrode, a continuous and interconnected solid-phase dual-ion transport network is constructed, eliminating interfacial ion transport barriers, significantly reducing interfacial impedance, and significantly improving lithium-ion conductivity and dual-ion transport uniformity. Combined with the intrinsic safety advantages and wide temperature range adaptability brought by the all-solid-state independent dense film structure, the lithium-sodium dual-ion all-solid-state battery of this invention has achieved comprehensive performance improvement in terms of capacity, cycle life and safety. It shows good technical potential in balancing low cost and high performance. While meeting the performance requirements of high safety, low cost, long cycle life and wide temperature range, it provides a practical and feasible technical path for the industrial application of lithium-sodium dual-ion all-solid-state batteries.

[0098] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A lithium-sodium dual-ion all-solid-state battery, having a layered all-solid-state stacked structure, comprising a positive electrode, a lithium-sodium dual-ion mixed solid electrolyte film, and a negative electrode sequentially bonded together, characterized in that, The positive electrode sheet comprises a positive electrode main material and a first lithium-sodium dual-ion mixed solid electrolyte. The positive electrode main material is a compound of vanadium-based polyanionic sodium salt and vanadium-based polyanionic lithium salt in a mass ratio of 1:1 to 1:

5. The negative electrode sheet comprises a negative electrode main material and a second lithium-sodium dual-ion mixed solid electrolyte. The negative electrode main material is a composite of silicon-carbon material and soft carbon material in a mass ratio of 1:1 to 1:

5. The first lithium-sodium dual-ion mixed solid electrolyte, the lithium-sodium dual-ion mixed solid electrolyte film layer, and the second lithium-sodium dual-ion mixed solid electrolyte are all mixtures of lithium-ion solid electrolyte and sodium-ion solid electrolyte.

2. The lithium-sodium dual-ion all-solid-state battery according to claim 1, characterized in that, The vanadium-based polyanionic sodium salt includes one of sodium vanadium phosphate, sodium vanadium pyrophosphate, and sodium vanadium fluorophosphate. The vanadium-based polyanionic lithium salt includes one of lithium vanadium phosphate, lithium vanadium pyrophosphate, and lithium vanadium fluorophosphate.

3. The lithium-sodium dual-ion all-solid-state battery according to claim 1, characterized in that, In the positive electrode sheet, the total mass ratio of the positive electrode main material is 50% to 70%, and the mass ratio of the first lithium-sodium dual-ion mixed solid electrolyte is 30% to 50%.

4. The lithium-sodium dual-ion all-solid-state battery according to claim 1, characterized in that, In the negative electrode sheet, the total mass ratio of the negative electrode main material is 50% to 70%, and the mass ratio of the second lithium-sodium dual-ion mixed solid electrolyte is 30% to 50%.

5. The lithium-sodium dual-ion all-solid-state battery according to claim 1, characterized in that, In the lithium-sodium dual-ion mixed solid electrolyte membrane, the mass ratio of the lithium-ion solid electrolyte to the sodium-ion solid electrolyte is 1:5 to 5:

1.

6. The lithium-sodium dual-ion all-solid-state battery according to claim 1, characterized in that, The positive electrode and / or the negative electrode further comprise a conductive agent and a first binder; the conductive agent is one or more of carbon-based conductive agents SP, VGCF, CNT, and Ketjen Black; the first binder is a polymeric binder.

7. The lithium-sodium dual-ion all-solid-state battery according to claim 1, characterized in that, The lithium-sodium dual-ion mixed solid electrolyte membrane layer also includes a second binder, the second binder having a mass ratio of 1-5% in the lithium-sodium dual-ion mixed solid electrolyte membrane layer.

8. A method for preparing a lithium-sodium dual-ion all-solid-state battery as described in claim 1, characterized in that, Includes the following steps: S1. Positive electrode preparation: Vanadium-based polyanionic sodium salt and vanadium-based polyanionic lithium salt are mixed to obtain the positive electrode main material. The positive electrode main material, the first lithium sodium dual ion mixed solid electrolyte, the conductive agent and the binder are added to the solvent to make a positive electrode slurry. The positive electrode sheet is obtained by coating, drying and rolling. S2. Preparation of all-solid electrolyte membrane: Lithium-ion solid electrolyte and sodium-ion solid electrolyte are mixed to obtain lithium-sodium dual-ion mixed solid electrolyte. The lithium-sodium dual-ion mixed solid electrolyte and binder are added to a solvent to make an electrolyte slurry. The all-solid electrolyte membrane is obtained by coating, solvent evaporation, curing and peeling. S3. Negative electrode preparation: Silicon-carbon material and soft carbon material are mixed to obtain the negative electrode main material. The negative electrode main material is mixed with a second lithium-sodium dual-ion mixed solid electrolyte, a conductive agent and a binder in a solvent to make a negative electrode slurry. After coating, drying and rolling, a negative electrode sheet is obtained. S4. Battery assembly: The positive electrode, the all-solid electrolyte membrane, and the negative electrode are sequentially bonded together and then packaged to obtain the lithium-sodium dual-ion all-solid-state battery.

9. The preparation method according to claim 8, characterized in that, In step S1, the drying includes preheating drying and vacuum drying; And / or, in step S2, the solvent evaporates at room temperature, and the curing includes vacuum drying at 80~120°C.

10. An electrical appliance, characterized in that, Including the lithium-sodium dual-ion all-solid-state battery as described in claim 1.

Citation Information

Patent Citations

  • Preparation method of lithium-sodium dual-ion positive electrode material, lithium-sodium dual-ion positive electrode material and secondary battery

    CN117638052A